Self-portrait images for mobile application - Teh, Phoey Lee *; Kabbany, Nael; Chan, Kei Jun (Springer, 2013)
Self-portrait using mobile phones has been a popular trend among backpackers, teenagers and travellers. The usage of mobile devices had been escalating over the years, as it is more convenient and portable. However, there were constraints in terms of camera view and angle the mobile devices can capture. Based on my preliminary research, the major problems faced by most backpackers concerns (i) hand distance, (ii) angle and view captured, and (iii) no alternative mechanism or functions in mobile devices that can capture a larger panoramic view in self-portrait. This proposal intends to study the current strategies used by travelers in taking self-portrait by using mobile devices and investigate future mobile image application. The subjects in this study include travellers (backpackers, people travelling alone) and social network users as viewers. The evaluation is to find out if a model of “destination image measurement” could be an attribute towards enhancing mobile application in the future. The concept of destination image measurement has four-distinct components; functional characteristics, psychological characteristics, holistic and attributes. The framework is to establish a strategy to improve self-portrait capturing using mobile devices and the evaluation outcome will be a measurement technique in capturing a more effective self-portrait.